New Azaphilones from Nigrospora oryzae Co-Cultured with Beauveria bassiana - Zhang, Zhuo-Xi; Yang, Xue-Qiong; Zhou, Qing-Yan; Wang, Bang-Yan; Hu, Ming; Yang, Ya-Bin; Zhou, Hao; Ding, Zhong-Tao (Molecules (Basel, Switzerland), 2018)
In this study, the co-culture of Nigrospora oryzae and Beauveria bassiana, the endophytes in the seeds of Dendrobium officinale, were examined for metabolite diversity. Five new azaphilones were isolated, and their structures were determined by spectral analysis. In terms of azaphilones, compound 2 had an unprecedented skeleton, with a bicyclic oxygen bridge. The antifungal selectivities of the metabolite produced by N. oryzae against its co-culture fungus, B. bassiana, and common pathogens exhibited competitive interaction in this mix-culture. Compounds 1 and 2 showed obvious nitric oxide (NO) inhibitory activity with ratios of 37%, and 39%, respectively, at a concentration of 50 μM.